Preliminary study on the use of contrast ultrasound in the preoperative workup of patient-candidates for carotid endarterectomy - Marco Campolmi, MD; Sara Speziali, MD; Elena Giacomelli, MD, PhD; Lapo Dolfi, MD; Walter Dorigo, MD; Raffaele Pulli, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
This study aimed to prospectively assess the use of the ultrasound signal amplifier in preoperative color Doppler ultrasound (DUS) evaluation of carotid plaques in asymptomatic patients eligible for surgical correction. Between November 2022 and May 2023, 21 patients with asymptomatic carotid stenosis were enrolled. Each patient underwent DUS, contrast-enhanced ultrasound (CEUS), and computed tomography angiography (CTA) during the preoperative workup. Data on demographics, clinical characteristics, risk factors, comorbidities, and therapy were collected. The degree of stenosis was analyzed using North American Symptomatic Carotid Endarterectomy Trial criteria, comparing DUS, CEUS, and CTA with statistical tests. Hemodynamic parameters (peak systolic velocity, end-diastolic velocity, internal carotid artery/common carotid artery ratio) and plaque morphology (juxtaluminal black areas, discrete white areas, and intraplaque neovascularization) were assessed. CEUS examination demonstrated a significantly higher stenosis degree (72%) compared with DUS (68%; P < .001) and differed from CTA (80%; P = .004). Hemodynamic parameters were also higher with CEUS (peak systolic velocity, 321 cm/sec vs 249 cm/sec; end-diastolic velocity, 92 cm/sec vs 88 cm/sec; internal carotid artery/common carotid artery ratio, 4.4 vs 3.8; all P < .001). CEUS examination identified irregular plaque margins more frequently (15 cases vs 8 cases), larger juxtaluminal black areas (17 cases vs 7 cases, mean diameter 3.3 mm vs 2.7 mm), and discrete white areas (6 vs 0). Neovascularization was observed in 10 plaques via CEUS examination. These findings suggest that CEUS examination is a safe, cost-effective, and efficient noninvasive tool for preoperative carotid plaque assessment, offering higher resolution and more detailed plaque characterization compared with DUS. Despite the limited sample size, CEUS examination provides valuable insights into plaque morphology and embolic risk profile. The CEUS examination needs to be validated with larger multicenter cohorts.